Perbandingan Disiplin Kerja antara Pegawai Negeri Sipil dengan Pegawai Tidak Tetap pada Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Wajo - Maskurniawan Maskurniawan; Yusran Yusran; Burhanuddin Burhanuddin (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
Good discipline is a form of action to obey and do something in accordance with values ​​and rules that are believed to be a responsibility, not only companies/government agencies must show good work discipline. Civil servants and non-permanent employees in government agencies are management tools used to improve the quality of decision making and accountability in order to assess the success or failure of implementing activities in accordance with predetermined goals in order to realize the vision and mission of a government agency. In conducting research, the author used a comparative method (comparison). Meanwhile, this method is to help analyze data and facts obtained from respondents, using quantitative analysis methods with statistical formulas. The results of this research show that there is a significant comparison between the work discipline of civil servants and non-permanent employees with a score difference of 1.2. So it can be interpreted that civil servants have greater work discipline than non-permanent employees, even though the results of the questionnaire distribution are both very good.